UKURAN PERUSAHAAN SEBAGAI PEMODERASI : PENGUNGKAPAN ESG - Nurcahyono, Alfin; Rejeki, Dewi (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2025)
This study aims to find out and analyze the influence of Environmental, Social, and Governance (ESG) Disclosure on Company Financial Performance with Company Size as a Moderator in Mining Companies Listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 Period. The sample determination method uses purposive sampling with a total of 23 research samples from 23 companies for 5 years with a total of 115 sample data. The data analysis methods used were multiple linear regression analysis and Moderated Regression Analysis (MRA) using IBM SPSS software version 27. The results of this study show that only Environmental disclosure has a positive effect on Financial Performance, while Social disclosure has a negative effect and Governance disclosure has no effect. The size of the company itself is not able to moderate the influence of Environmental, Social and Governance (ESG) disclosures. The implications of this study show that each dimension (Environmental, Social, Governance) has a different influence on financial performance although the results support the theory of legitimacy and stakeholders, especially the importance of environmental issues as the main focus of investors and society. The company focuses more on environmental disclosure and is selective in social programs. Investors use the environmental aspect as the main indicator and always be careful about social & governance. Regulators encourage quality environmental disclosure; evaluation of social and governance standards to have an economic impact.